Papers of Eric Ernest Williams - Williams, Eric Ernest, 1911-; White, T. W. (Thomas Walter), Sir, 1888-1957.; Williams, Eric Ernest, 1911- (1957)
The papers include correspondence between Eric Williams and Sir Thomas White relating to William's book, "Complete and free". Also includes a review of "Complete and free" from the"Melbourne age", 22 June 1957, a review written by White and an article on White's famous escape from a Turkish prison in 1918.
Manuscript reference no. : MS 9377.
Eric Williams, famous British World War II escapee and author of "The wooden horse" (1949), "The tunnel" (1951), "The escapers" (1953) and "Complete and free" (1957).
Keywords: Williams, Eric Ernest, -- 1911- -- Archives; Authors, British -- Archives; Authors